The Influence of E-WOM And Brand Image On Consumer Purchase Decisions for Pixy Cosmetic Products - Nabila, Jihan; Wijaya, Rahmad; Dewayani, Eka Kadharpa Utama (Universitas Muhammadiyah Malang, 2024)
This research was conducted to determine and analyze the influence of e-WOM and brand image on purchasing decisions. This research uses quantitative methods. The data collection technique in this research uses a questionnaire. A sample of 120 was carried out using purposive sampling. Multiple linear regression analysis technique. The research results found that e-WOM has a positive and significant effect on purchasing decisions and brand image has a positive and significant effect on purchasing decisions. E-wom and brand image have a simultaneous influence on purchasing decisions.